Marktäckande, lågväxt vegetation på ställverksmark - Johansson, Jenny (2006)
Unwanted vegetation on the land of electric transforming stations is a problem, in the sense that it contributes to higher fire risks and also constitutes an obstacle for people performing maintenance operations at the station. Such unwanted vegetation is controlled using herbicides and mechanical measures. Since the use of herbicides implies environmental hazards, there is a need to find alternative ways of fighting the unwanted vegetation.